Ionic Size Effect on Equilibrium Constant for Some Uni-Bivalent Exchange Reactions - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
Ion exchange resins Amberlite IRA-400 in chloride and iodide form were equilibriated respectively with oxalate and sulphate ion solution of seven different concentrations from 0.010 M to 0.050 M in the temperature range of 30 to 45°C. The equilibrium constant (K) values calculated for both Cl-/C2O42- and I-/SO42- uni-bivalent exchange increases with increase in temperature. The K value at 30°C for Cl-/C2O42- ion exchange was calculated to be 19.5 which was higher than 0.250 for I-/SO42- exchange at same temperature. The variation in values of K was due to the difference in ionic size of exchangeable oxalate and sulphate ions in solution.